“Literally, there were only a few steps between the cold and warmth, and between darkness and light.” The Image of the City in "Smutna Wenecja" by Wacław Kubacki - Kuran, Magdalena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The article discusses the image of the city presented in the novel Smutna Wenecja by Wacław Kubacki, an outstanding literary historian, and how the writer’s interests and experiences influenced the topic and the character of the work (he utilised his journals). The city depicted by Kubacki seems to possess a dichotomous nature. The Venetian garden of the arts and the mecca of academics was contrasted with the Venice of poor and foul recesses. The author contrasted the Venice of tourists’ “unbridled excess” with the reality of the life of Venice’s proletariat. The article indicates the linguistic and compositional means which the writer used to reflect that duality, beauty, and ugliness. The article also indicates the dominant features of the novel, i.e. intellectualism and sensoriness.